Praxis Blue Ocean Strategic: (Student Selection) PPDB Process in Educational Institutions During The Covid-19 Pandemic - Muhammad Solikhin; Naimah Naimah (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Student Screening (PPDB) in educational institutions during the Covid-19 pandemic with a blue ocean strategy is a solution in optimizing the PPDB process in schools. This study aims to determine whether praxisblue ocean strategies to determine success in PPDB during the Covid-19 pandemic, as well as knowing how the praxis process blue ocean strategy in educational institutions during the Covid 19 pandemic, a case study at SMK Muhammadiyah Prambanan. The method used is descriptive analysis using a qualitative approach. This study uses primary data obtained through interviews with key informants and secondary data in the form of supporting documents or literature related to research. The results showed that the implementation of the strategyblue ocean in the PPDB process in educational institutions (schools) during the Covid-19 pandemic, this became a strategic step in formulating a method/method in the process of selecting new students. In its implementation, it can be done by making new breakthroughs by strengthening the internal potential of schools (POIS) and supported by strengthening the four-step system consisting of eliminating (less effective strategies), reducing (strategies carried out by many competitors), increasing (internal potential of schools that are less effective). owned), and creating (innovation of the potential of the school). reducing (strategies carried out by many competitors), increasing (internal potential of schools that are less effective). owned), and creating (innovation of the potential of the school). reducing (strategies carried out by many competitors), increasing (internal potential of schools that are less effective). owned), and creating (innovation of the potential of the school).